Effect of Carbon and Nitrogen Sources on the Growth and Production of Cellulase Enzymes of a Newly Isolated Aspergillus sp. - Tong, Chow Chin; Rajendra, K. (1992)
The culture filtrate obtained from a newly isolated Aspergillus sp. exhibited good activities against the filter paper as substrate. The optimum temperature and pH values for growth were 3'?C and 6.5, respectively. However, the optimum temperature and pH for the activities of the cellulase enzymes were recorded as 44'C and 4.5, respectively. Production of the enzymes in liquid medium reached its maximum level (9 units/ml) at the 15th day of incubation with an incubation period of up to 21 days. From the various carbon and nitrogen sources tested, carboxymethyl cellulose (medium viscosity) and (NH) 2 Fe(SO)2' 6H20 were found to be the best for cellulase enzyme production, whereas cellulose powder and NH/103 enhanced mycelial growth.